ANALYST FLATTERY, CEO NARCISSISM, AND CEO COMMUNICATION SPECIFICITY - Schill, Ann Kathrin; Boutalikakis, Angelo; Hawighorst, Friederike; Graf-Vlachy, Lorenz; König, Andreas (Academy of Management Annual Meeting Proceedings, 2022)
We study how securities analysts’ use of flattery toward a CEO affects the degree to which that CEO communicates with higher specificity, rather than vaguely. CEO communication specificity is important for analysts as it substantially facilitates their work. However, CEOs might have little incentive to communicate with high specificity as it narrows CEOs’ strategic discretion. We argue that flattery-a ubiquitous social influencing behavior-enables analysts to render CEOs more likely to overcome their preference for vague communication because it invokes norms of reciprocity in the CEO and enhances the CEO’s self-esteem. Ultimately, the more an analyst flatters a CEO, the greater that CEO’s communication specificity. Moreover, integrating CEO narcissism research, we argue that analyst flattery provides “narcissistic supply” such that the positive effect of analyst flattery on CEO communication specificity increases to the extent of the focal CEO’s narcissism. Data from 2,159 dyads of analyst questions and CEO answers in quarterly earnings calls of U.S. hard- and software as well as pharmaceutical firms preliminarily support our hypotheses. Our theorizing and findings introduce a novel outside-in perspective of social influencing mechanisms-particularly flattery-at the executives/capital-markets interface. It also answers strategic leadership scholars’ calls to illuminate the “relational black box” of CEOs’ interactions with external stakeholders.
CRIS-Team Scopus Importer:2026-04-08